Climate policy portfolios that accelerate emission reductions [data] - Arvanitopoulos, Theodoros; Bulian, Simon; Wilson, Charlie; Jordan, Andrew J.; Tosun, Jale; Vasilakos, Nicholas (Universität, 2026)
The corpus of national climate policies continues to grow - but to what effect? Using data on 3,917 policy instruments across 43 OECD countries and major emerging economies from 2000-2022, we show that national climate policy portfolios specializing in instrument types and sectors are associated with faster reductions in fossil CO2 emission intensity. Supported by exemplar country case studies, we also provide quantitative evidence that the effectiveness of climate policy is amplified by long-term emission reduction targets and the presence of dedicated governmental bodies including ministries and intergovernmental organisations. The cumulative effect of all climate policy portfolios over our study period amounts to 3.1 GtCO2 fewer emissions in 2022 relative to a no-policy counterfactual - substantially less than what’s needed to stay on track for the Paris Agreement goals.
Gefördert durch: EDITS (Ministry of Economy, Trade, and Industry (METI), Japan); European Research Council: ERC Grant #101003083; Centre for Climate Change Economics and Policy (CAST): UK ESRC Grant #ES/S012257/1; European Research Council: ERC Grant #882601; The Research Council of Norway: Grant #335073; EU: EU Horizon Grant #101081377
Keywords: Forschungsdaten; Datenbank